2021
DOI: 10.1039/d1dt01752g
|View full text |Cite
|
Sign up to set email alerts
|

Schiff-base [4]helicene Zn(ii) complexes as chiral emitters

Abstract: The controlled preparation of chiral emissive transition metal complexes is fundamental in the field of circularly polarized luminescence (CPL) active molecular materials. For this purpose, enantiopure Zn(II) complexes 1-2 based...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…5b) and is comparable with the reported CPL intensity of chiral Schiff-base [4] helicene Zn 2+ complexes. 52…”
Section: Papermentioning
confidence: 99%
“…5b) and is comparable with the reported CPL intensity of chiral Schiff-base [4] helicene Zn 2+ complexes. 52…”
Section: Papermentioning
confidence: 99%
“…Zinc( ii ) and cadmium( ii ) complexes establish one of the most important classes of emissive compounds. 71–121 Earlier, we synthesized a series of mononuclear zinc( ii ) and cadmium( ii ) complexes with hybrid ligands containing a 2,2′-bipyridine moiety and natural terpene (+)-limonene or (+)-3-carene moieties and demonstrated that they exhibit luminescence with the quantum yield increasing in the following order: free ligand < cadmium( ii ) complex < zinc( ii ) complex. 122 The complexes with the limonene derivative demonstrate excitation wavelength–dependent emission with nanosecond and microsecond lifetimes of the excited states.…”
Section: Introductionmentioning
confidence: 99%
“…[10,11] Moreover, very recently, the use of azahelicene appended pyridine ligands [8] allowed the preparation of an ytterbium(III) complex showing strong magneto-chiral dichroism. [12] In the frame of our own interest in functional helicenes, [13,14] and their transition metal complexes, [9,15] we have recently reported the series of 2,6bis(pyrazol-1-yl)pyridine (1-bpp) ligands substituted by racemic [4]-, [5]-and [6]helicene units in the 4-position of the pyridine ring, together with the photophysical properties of their luminescent Re(I) and Ru(II) complexes. [16] While a large variety of functionalized 1-bpp and corresponding transition metal complexes have been reported, [17,18] chiral derivatives have received little attention so far, [19,20] especially driven by catalytic applications, [21,22] but not for emission or chiroptical properties.…”
Section: Introductionmentioning
confidence: 99%